Protocol for systematic review and meta-analysis of treatment success rate among adult patients with tuberculosis in sub-Saharan Africa - Izudi, Jonathan; Semakula, Daniel; Sennono, Richard; Tamwesigire, Imelda K.; Bajunirwe, Francis (BMJ open, 2018)
Tuberculosis (TB) is a leading cause of mortality globally. Despite being curable, treatment success rates (TSRs) among adult patients with bacteriologically confirmed pulmonary TB (BC-PTB) in sub-Saharan Africa (SSA) differ considerably. This protocol documents and presents an explicit plan of a systematic review and meta-analysis to summarise TSR among adult patients with BC-PTB in SSA.Two reviewers will search and extract data from MEDLINE, EMBASE, Ovid, Cumulative Index to Nursing and Allied Health Literature and Web of Science electronic databases. Observational and interventional studies published between 1 July 2008 and 30 June 2018, involving adult patients with BC-PTB will be eligible. Data abstraction disagreements will be resolved by consensus with a third reviewer, while percentage agreement computed with kappa statistics. TSR will be computed with Metaprop, a Stata command for pooling proportions using DerSimonian and Laird random effects model and presented in a forest plot with corresponding 95% CIs. Heterogeneity between included studies will be assessed with Cochran’s Q test and quantified with I-squared values. Publication bias will be evaluated with funnel plots and tested with Egger’s weighted regression. Time trends in TSR will be calculated with cumulative meta-analysis.